Bridging the Information Gap for Increased Livestock Productivity in Tanzania - International Institute of Tropical Agriculture; International Livestock Research Institute (International Food Policy Research Institute, 2021)
This dataset is generated from the study conducted to evaluate the effect of information and communications technology (ICT) based extension services on knowledge, attitudes, and practices among smallholder farmers in Tanzania. A baseline survey of randomly selected 100 dairy farmers was conducted to collect information on the basic characteristics of the sample. After the baseline survey, short and clear messages about dairy and poultry production were disseminated over 14 weeks using the MWANGA platform, a short message service. An endline survey along with focus group discussion was conducted at five sites in the Babati District of Tanzania. Data collected included uptake of improved forages, knowledge in the use of forages and animal husbandry, and practices in animal production among others.